2017
DOI: 10.1108/jap-03-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

10,000 Voices: service users’ experiences of adult safeguarding

Abstract: Purpose-This paper describes a small scale pilot study undertaken in Northern Ireland to gather service user feedback from individuals who have been subject to adult safeguarding procedures. Design-The aims, methods and findings of the 'Adult Safeguarding: 10,000 Voices' pilot project are presented. Findings-The pilot project highlighted how an initiative which captures the experiences of patients, service users, carers and staff in the health and social care sector (10,000 Voices) could be successfully adapte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…There is scope to develop these further and to share their findings more widely. There is particular scope to widen involvement in their design and conduct, following key innovations such as Burns (2018) and Montgomery et al (2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is scope to develop these further and to share their findings more widely. There is particular scope to widen involvement in their design and conduct, following key innovations such as Burns (2018) and Montgomery et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our means of accessing participants relied on collaboration with service-providing agencies. There is a documented tendency towards greater protectionism amongst organisations operating in this 'gatekeeper' role (Montgomery et al, 2017;Munro et al, 2005). In study 2 there was a staged procedure whereby samples were identified by a senior social work contact, then key workers invited service users to participate where they felt this was appropriate.…”
Section: Researching Experience Of the Scottish Legislation: Evaluatimentioning
confidence: 99%
“…This is particularly pertinent in light of positive developments in other aspects of health and social care, in which the significance afforded to "experts by experience" has enabled individuals to gain more control of their care and to contribute to service development (SCIE, 2011). Partnerships with service users have been developed to create changes in the way health and social care systems are designed, planned, commissioned and delivered (Montgomery et al, 2017), with local regions of the UK requiring service users to take a role in policy development. For example, under the Health and Social Care Reform Act (NI) (2009), health and social care bodies in NI must seek the views of service users and carers, often referred to as Personal and Public Involvement (PPI).…”
Section: Discussionmentioning
confidence: 99%
“…In (Montgomery, et al, 2017). More standard options for people to share their views and experiences include being members or organisers of advisory groups (Hudson, 2015).…”
Section: What People With Lived Experience Want To Engage In and Howmentioning
confidence: 99%
“…Overall people with lived experience get involved in research activities such as identifying research questions, designing studies, improving recruitment, collecting and analysing data, co-producing outputs and disseminating findings (Morgan et al, 2016;Szmukler et al, 2011;Lindenmeyer et al, 2007;Green et al, 2016). Other roles more akin to "consultant" or "expert advisor" include helping with projects and testing data gathering approaches (Montgomery et al, 2017). More standard options for people to share their views and experiences include being members or organisers of advisory groups (Hudson, 2015).…”
Section: What People With Lived Experience Want To Engage In and Howmentioning
confidence: 99%